PATENT CERTIFICATES AS FIDUCIARY ASSETS: A LEGAL REVIEW BASED ON LAW NUMBER 13 OF 2016 AND LAW NUMBER 42 OF 1999 - Achmad Dahlan; Basyarudin Basyarudin (Legis Nexus: Jurnal Ilmu Hukum, 2026)
Amid the transformation toward an innovation-based economy, intellectual property particularly patents plays a vital role as a strategic asset with significant economic value. This article analyzes the legality of using patent certificates as fiduciary collateral within the Indonesian legal system, based on Law No. 13 of 2016 on Patents and Law No. 42 of 1999 on Fiduciary Security. Employing a normative juridical approach, this study explores the legal basis, material and formal requirements, and the legal implications for both patent holders and creditors. The findings indicate that while patent certificates can serve as fiduciary collateral, their implementation faces regulatory and practical challenges, including ambiguities in economic valuation procedures and potential contractual conflicts. Therefore, regulatory reinforcement and institutional understanding are essential for patents to function effectively as financing instruments. This study highlights the importance of recognizing intellectual property as a legitimate collateral object to support innovation-driven economic growth and ensure balanced legal protection